Cu(i) complexes obtained via spontaneous reduction of Cu(ii) complexes supported by designed bidentate ligands: bioinspired Cu(i) based catalysts for aromatic hydroxylation. Issue 39 (1st October 2020) - Kumari, Sheela; Muthuramalingam, Sethuraman; Dhara, Ashish Kumar; Singh, U. P.; Mayilmurugan, Ramasamy; Ghosh, Kaushik
Abstract : Cu(i ) complexes were synthesized via spontaneous reduction and X-ray crystal structure of complex 1 was determined. Direct hydroxylation of benzene to phenol afforded selectivity up to 98%. KIE values of 1.69–1.71 supported radical based mechanism. Abstract : Copper(i ) complexes [Cu(L 1–7 )2 ](ClO4 ) (1–7 ) of bidentate ligands (L 1 –L 7 ) have been synthesized via spontaneous reduction and characterized as catalysts for aromatic C–H activation using H2 O2 as the oxidant. The single crystal X-ray structure of 1 exhibited a distorted tetrahedral geometry. All the copper(i ) complexes catalyzed direct hydroxylation of benzene to form phenol with good selectivity up to 98%. The determined kinetic isotope effect (KIE) values, 1.69–1.71, support the involvement of a radical type mechanism. The isotope-labeling experiments using H2 18 O2 showed 92% incorporation of 18 O into phenol and confirm that H2 O2 is the key oxygen supplier. Overall, the catalytic efficiencies of the complexes are strongly influenced by the electronic and steric factor of the ligand, which is fine-tuned by the ligand architecture. The benzene hydroxylation reaction possibly proceeded via a radical mechanism, which was confirmed by the addition of radical scavengers (TEMPO) to the catalytic reaction that showed a reduction in phenol formation.